Preparation and Characterization of Fe-Based Metallic Glasses with Pure and Raw Elements - Seghairi, Nassima (2012)
Amorphous alloys with a composition (at.%) Fe48Cr15Mo14C15B6Y2 were prepared by using either pure elements(alloy B1) or a commercial AISI430 steel as a base material (B2). When prepared from pure elements, alloy (B1)could be cast in plate form with a fixed thickness of 2mm and variable lengths between 10 and 20mm by means of copper-mold injection in an air atmosphere. In the case of alloy B2, prepared by using commercial grade raw materials, rods of 2mm diameter are obtained. Ribbons (B1 and B2) of width 5mm and thickness about 30 m are prepared from the arc-melted ingots using a single roller melt spinner at a wheel speed of 40 m/s. The thermal and structural properties of the samples are measured by a combination of differential scanning calorimetry (DSC), x-ray diffraction and scanning electron microscopy. Chemical compositions are checked by energy dispersive spectroscopy analysis. X-ray diffraction and scanning electron microscopy observations confirm that an amorphous structure is obtained in all the samples. A minor fraction of crystalline phases (oxides and carbides) is detected on the as-cast surface. Values of hardness and Young modulus were measured by nanoindentation for both the alloys. The effects of adverse casting conditions (such as air atmosphere, nonconventional injection copper mold casting and the partial replacement of pure elements with commercial grade raw materials) on the glass formation and properties of the alloy are discussed.